An approach for High Density Impulse Noise Removal using Modified Median Filter - Sudha Tak; Prof. Sandeep Gangane (Journal of Electronic Design Engineering, 2018)
Images are imitations of real world objects. Often an image is a two dimensional (2D) signal f(x,y) represent the amplitude or intensity of the image. In the Transmission of images, they are corrupted by salt and pepper noise, due to faulty communications. Salt and Pepper noise is also known as Impulse noise. The intention of filtering is to eradicate the impulses so that the noise less image is fully enhanced with slightest signal distortion. The best-known and most commonly used nonlinear digital filters, based on order statistics are median filters, also known as Simple Median Filter (SMF). Median filters are recognized for their capability to remove impulse noise without damaging the edges. The main aim of this work is to modify the existing median filters and implement the modified median filter for reduction of high density impulse noise (salt & pepper noise). Then evaluate the performance of the algorithm using MSE & PSNR parameters.